2003
DOI: 10.4321/s0212-71992003000200007
|View full text |Cite
|
Sign up to set email alerts
|

Anemia hemolítica autoinmune: una rara complicación de la colitis ulcerosa

Abstract: La primera descripción de una anemía hemolítica autoinmune (AHAI) en el seno de una colitis ulcerosa (CU), fue realizada en 1955 por Lorber (4). En 1964, Edwards encontró un nuevo caso entre 624 pacientes con el diagnóstico de CU (5). En 1967, Ormerod presentó otro caso entre 479 pacientes (6). En un estudio prospectivo realizado en Portugal en 1991 y llevado a cabo en 180 pacientes, se concluyó que la frecuencia de esta complicación era del 0,6% (7). En una serie de Oxford de 1989 con 858 pacientes se encontr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The diagnosis of AIHA includes a positive direct Coombs test that detects IgG or complement absorbed onto red blood cells. However, studies have shown that approximately 1.82% of UC patients without signs of hemolysis can have a positive direct Coombs test (Valderrama Rojas, Rodriguez Gorostiza et al, 2003). Systemic steroids are the first line of therapy, produce remission in 21% to 50% of cases, and should be continued for 3 weeks before being considered ineffective (Gumaste, Greenstein et al, 1989;Veloso et al, 1991).…”
Section: Autoimmune Hemolytic Anemiamentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of AIHA includes a positive direct Coombs test that detects IgG or complement absorbed onto red blood cells. However, studies have shown that approximately 1.82% of UC patients without signs of hemolysis can have a positive direct Coombs test (Valderrama Rojas, Rodriguez Gorostiza et al, 2003). Systemic steroids are the first line of therapy, produce remission in 21% to 50% of cases, and should be continued for 3 weeks before being considered ineffective (Gumaste, Greenstein et al, 1989;Veloso et al, 1991).…”
Section: Autoimmune Hemolytic Anemiamentioning
confidence: 99%
“…However, AIHA should be suspected in patients with anemia, painless jaundice, and unconjugated hyperbilirubinemia (Gumaste et al, 1989;Valderrama Rojas et al, 2003). The diagnosis of AIHA includes a positive direct Coombs test that detects IgG or complement absorbed onto red blood cells.…”
Section: Autoimmune Hemolytic Anemiamentioning
confidence: 99%